EXTRADURAL DERMOID TUMORS OF THE POSTERIOR FOSSA (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Dermoid tumors in children usually occur in two locations: in the anterior fontanel and on the occipital scales. The exclusive site of occurrence of a dermoid cyst of the posterior fossa is the extradural space. Only six previously similar cases have been described in the literature. A series of pediatric lesions have been reviewed and children with extradural posterior fossa dermoids have been reported..